Manejo de los trastornos hipertensivos durante el embarazo - Freire Tinoco, Joselyn Paulette (Machala : Universidad Técnica de Machala, 2024)
Introduction: Hypertensive disorders in pregnancy (HDP) are a cause of maternal, fetal and neonatal morbidity and mortality, complicating gestational states around 5 to 10% worldwide, a percentage on the rise due to risk factors and cardio-metabolic alterations. Preeclampsia has an incidence of 2 to 8% of which 1 to 5% corresponds to eclampsia, representing 75% of the complications that cause maternal death. Through a search of scientific databases such as Medline, MedicLatina, Pubmed and Academic Search Premier, we analyze the recommended management protocols to be followed in pregnant women with hypertensive disorders, describe their classification and identify the side effects of antihypertensive drugs for the mother and fetus. Development: HDP is suggested to adhere to the classification recommended by the ESC due to its close resemblance to that established by the CCS and ACOG, according to the clinical criteria and its characteristics. Conclusion: ASA and elemental calcium are recommended as prophylaxis for HDP. The management of HDP will depend on its categorization which corresponds to chronic hypertension, gestational hypertension, chronic hypertension + superadded preeclampsia and preeclampsia, subdivided into its severe hypertensive complications (eclampsia and HELLP syndrome). In case of mild to moderate hypertensive disorder, first line use of Alpha Methyldopa and second line use of labetalol, hydralazine or oral nifedipine is suggested. Similarly, in cases of severe hypertension, the therapy of choice is IV therapy such as labetalol or hydralazine, on the other hand, the Ecuador CPG and certain studies of developed countries indicate that short-acting oral nifedipine is the drug of choice prior to the placement of IV hypotensive agents.
Introducción: Los desórdenes hipertensivos en el embarazo (HDP) son causa de morbilidad y mortalidad tanto materna como fetal y neonatal, complicando estados gestacionales alrededor del 5 al 10% mundialmente, porcentaje en ascenso debido a factores de riesgo y alteraciones cardio-metabólicas. La preeclampsia tiene una incidencia del 2 al 8% de la cual corresponde 1 al 5% a eclampsias; representando el 75% de las complicaciones que producen muerte materna. Mediante una búsqueda de bases de datos científicas como Medline, MedicLatina, Pubmed y Academic Search Premier, se analiza los protocolos de manejo recomendados a seguir en gestantes con trastornos hipertensivos, describir su clasificación e identificar los efectos secundarios de los medicamentos antihipertensivos para la madre y el feto. Conclusión: Se recomienda para los HDP como profilaxis el AAS y calcio elemental.. El manejo de los HDP dependerá de su categorización que corresponde a HTA crónica, Hipertensión gestacional, HTA crónica + preeclampsia sobreañadida y Preeclampsia, subdividida en sus complicaciones hipertensivas severas (eclampsia y síndrome de HELLP). En caso de un trastorno hipertensivo leve a moderado, se sugiere el uso de 1era línea la Alfa Metildopa y de segunda línea: labetalol, hidralazina o nifedipino oral. Del mismo modo, en casos de HTA severa, la terapia de elección son IV como el labetalol o la hidralizina, por otro lado, la GPC del Ecuador y ciertos estudios de países desarrollados, indican que la nifedipino oral de accion corta es el medicamento de elección previo a la colocación de los hipotensores IV.
Keywords: MANEJO; TRASTORNOS HIPERTENSIVOS; EMBARAZO